PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA MELALUI MOTIVASI KERJA (Studi Pada Karyawan Bank Riau Kepri Cabang Utama Pekanbaru) - Sulistia, Lola (Jurnal Tepak Manajemen Bisnis, 2017)
This study aimed to analyze the effect of competence and career developmentto job satisfaction through employee motivation Main Branch Bank Riau RiauPekanbaruJob satisfaction is one of the human output of a series of processes in organizationalbehavior. This attitude is fueled by motivation, competency and career development.Motivation affects the behaviors of employees, and job satisfaction. Competence isone reason that causes motivated employees, but it also affects the career development ofemployee motivation.The analysis tool used is path analysis. To test the effect of variablepartially used test of significance using the partial effect of Ã¡ 5%. To test the effect ofmediation used path analysis (Test Path). The object of this study are employees of BankRiau Riau Main Branch Pekanbaru, with a sample or respondents were 110 people.Theconclusion of this study is variable competence and career development of positive andsignificant impact on work motivation variable, the variable competence and career developmentof positive and significant impact on job satisfaction variables From the resultsof this research can be pursued to increase job satisfaction in the neighborhoodBanki Riau Riau Main Branch Pekanbaru by implementing competency and career developmentfor correct and enhance work motivation, as one of the maintenance effort ofhuman resources within the organization